1986
DOI: 10.1159/000242536
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and Femoral Blood Flow Autoregulation in Developing Swine

Abstract: Pressure-flow relationships (P/F) in the small intestine or hindlimb circulation were used to examine autoregulation in 104 swine, aged 1 day to 2 months and anesthetized with pentobarbital. The P/F were obtained while perfusion pressure was decreased by compression of the abdominal aorta for 2 min at each pressure. Readjustments in vascular resistance stabilized within 2 min. Intestinal flow decreased with each decrease in pressure in swine 2 weeks old or younger, but was well maintained by 1 month of age. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
5
19
0
Order By: Relevance
“…However, existing evidence suggests that its effect on blood pressure and heart rate is small or negligible at the doses used (26). Also, this anesthetic dosage maintains baroreceptor and peripheral vascular constrictor responses (27). From our data, a comparison of the control heart rates and blood pressure against a population of unaesthetized piglets (28) of the same age showed a slight difference in blood pressure (80 versus 82 mm Hg) and a resting heart rate about 15% higher (170 versus 198 bpm).…”
Section: Apnea and Hypertension Hypertension Developed In Syn-supporting
confidence: 49%
“…However, existing evidence suggests that its effect on blood pressure and heart rate is small or negligible at the doses used (26). Also, this anesthetic dosage maintains baroreceptor and peripheral vascular constrictor responses (27). From our data, a comparison of the control heart rates and blood pressure against a population of unaesthetized piglets (28) of the same age showed a slight difference in blood pressure (80 versus 82 mm Hg) and a resting heart rate about 15% higher (170 versus 198 bpm).…”
Section: Apnea and Hypertension Hypertension Developed In Syn-supporting
confidence: 49%
“…Characterization of intestinal blood flow and oxygenation in the developing animal, however, has only recently been initiated. The intestine of neonatal piglets appears to be more vulnerable than that of older piglets to reductions in perfusion pressure (12,13) and hemorrhage (14,15) yet it appears to be less susceptible to hypoxic damage induced by acute venous hypertension (1 6).…”
Section: Discussionmentioning
confidence: 99%
“…A broad tape ligature was placed around the ab dominal aorta above the celiac artery and the tip of the aortic pressure catheter and used to compress the aorta against a convex plastic plate, as reported in detail previously [1,12]. Autoregulatory capability was tested in all three circulations simultaneously by a single-step decrease in aortic pressure to 70-90% of control level, within the previously established auto regulatory ranges at different ages [ 1.…”
Section: Determination O F Autoregulatory Capability O F Regional Cirmentioning
confidence: 99%
“…We have reported that, during the first postnatal month, swine do not exhibit rest ing hindlimb blood flow autoregulation [1] but vigorous neural control of the femoral circulation [2], We next tested two hypothe ses: that hindlimb work would be accompa nied by the appearance of autoregulatory ca 1 Supported by National Heart. Lung and Blood Institutes, grant HL-21865.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation